SBC 컴퓨팅 환경에서 딥러닝을 이용한 자돈 압사 인식 성능 분석 - Taeyong Yun(윤태용); Yeseong Kang(강예성); Woongsup Lee(이웅섭) (한국정보통신학회논문지, 2024)
In this study, we aim to validate the use of Artificial Intelligence of Things (AIoT) for deep learning-based detection of piglet crushing incidents by sows in pig farms, a leading cause of piglet mortality. To achieve this, we developed a deep neural network based on the You Only Look Once (YOLO) model, which was trained to detect piglet crushing events in real-time. We then optimized the weights of the YOLO model using TensorFlow Lite, TensorRT, and edge TPU to ensure efficient operation on AIoT devices with limited computational resources. Finally, we compared the performance of the deep learning-based piglet crushing detection algorithm on various single-board computers (SBCs), including the Jetson Nano, Raspberry Pi, and Coral Dev Board, to validate its suitability for real-world applications. KCI Citation Count: 0